Developing the resilience of families with children with special needs - Enache, Rodica-Gabriela; Gîrlea, Florentina (Technium Social Sciences Journal, 2022)
People frequently seek counselling at times of crisis or change. A current precipitating event such as a major life event (e.g. from married to widowed or single, have children with special needs) may spur a person to seek help. Our objectives for this paper are: the assessment of resistance and attachment levels of the families with children with neuro-developmental disorders and evaluating how the parental quality of life is perceived after applying the individualized intervention on the child with special needs.